Reaktif Oksigen Spesies Pada Cedera Otak Traumatik - Suarjaya, I Putu Pramana; Bisri, Tatang; Wargahadibrata, A. Himendra (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2012)
Cedera otak traumatik menyebabkan mortalitas dan morbiditas karena terjadinya cedera primer yang diikuti oleh cedera sekunder. Cedera sekunder yang terjadi meliputi peningkatan asam amino eksitatif, ketidak seimbangan ion, penurunan kadar ATP, aktivasi enzim proteolitik dan stres oksidatif yang akan menyebabkan terjadinya disfungsi neuron sampai kematian neuron. Terdapat kaitan erat antara beratnya stres oksidatif yang terjadi dengan beratnya cedera otak yang terjadi, sebagai akibat terganggunya hemostasis kalsium, gangguan pembentukan energi dan meningkatnya proses peroksidasi lipid. Pada telaah ini didiskusikan bagaimana stres oksidatif yang terjadi pada cedera otak traumatik, dan pengaruhnya pada proses pathologi sedera otak traumatik.Reactive Oxygen Species in Traumatic Brain InjuryTraumatic Brain Injury (TBI) morbidity and mortality are due to primary and secondary injury. Primary injury is due to mechanical forces during the trauma process and secondary injury is subsequent process following the primary impact. This secondary injury processes involving increased excitatory amino acids, ionic imbalance, decreased ATP level, unusual proteolytic enzyme activity, and oxidative stress which contibute to delayed neuronal dysfunction and neuronal death. The mammalian brain is vulnerable to oxidative stress because of the high oxygen consumption needed for maintaining neuronal ion homoeostasis during the propagation of action potentials.There is a close relationship between degree of oxidative stress and severity of brain insults, which results from a perturbation of calcium homeostasis, energy metabolism, and increased lipid peroxidation. In this review we discuss oxidative stress during traumatic brain injury, and its implication on pathology of traumatic brain injury.